2022
DOI: 10.1037/fam0000987
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender-affirming care bans on transgender and gender diverse youth: Parental figures’ perspective.

Abstract: Transgender and gender diverse (TGD) youth in the United States are met with systemic barriers that affect their physical and mental health. Recent scholarship has found that TGD youth have been negatively impacted as a result of antitransgender federal, state, and local laws and bills. Given the crucial role of parental figures in the well-being of TGD youth (e.g., supporting their child's health-care decisions), parents can provide important insight about the experiences of their children as they navigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 53 publications
2
20
0
Order By: Relevance
“…Moreover, in alignment with recent studies on the effects of the bills from the perspective of parents of transgender youth (Abreu et al, 2021 , 2022 ; Kidd et al, 2021 ), qualitative themes also revealed that transgender youth and young adults had been impacted by the legislation in a host of ways, including mental health consequences, a decreased willingness to seek medical care of any kind, increased discrimination and other maltreatment, and heightened fears about disclosing their identities. Confirming prior findings (Meier et al, 2011 ; Tordoff et al, 2022 ), respondents also expressed that access to gender-affirming care has been integral for their mental health and that not having access would increase negative mental health symptoms and the risk of suicide.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Moreover, in alignment with recent studies on the effects of the bills from the perspective of parents of transgender youth (Abreu et al, 2021 , 2022 ; Kidd et al, 2021 ), qualitative themes also revealed that transgender youth and young adults had been impacted by the legislation in a host of ways, including mental health consequences, a decreased willingness to seek medical care of any kind, increased discrimination and other maltreatment, and heightened fears about disclosing their identities. Confirming prior findings (Meier et al, 2011 ; Tordoff et al, 2022 ), respondents also expressed that access to gender-affirming care has been integral for their mental health and that not having access would increase negative mental health symptoms and the risk of suicide.…”
Section: Discussionsupporting
confidence: 62%
“…The gender minority stress model was created to capture the various identity-related stressors that gender minorities (i.e., transgender, non-binary, and genderqueer people) experience and this model proposes that forms of systemic oppression, including policies that restrict the rights of gender minorities, are critical antecedents to the health and well-being of gender minorities (Hendricks & Testa, 2012 ; Testa et al, 2015 ). Applying this to the current context, as Abreu et al ( 2022 ) argued, “the antitransgender laws and bills being proposed and passed across the United States have contributed to structural stigma and gender minority stress for TGD [transgender] youth” (p. 3). Furthermore, the gender minority stress model also emphasizes the role of social support in the stress process such that getting affirmation for one’s identity from friends and family can improve outcomes (Testa et al, 2015 ).…”
Section: Legislation As a Mega-threatmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, antitransgender legislation targeting youth is increasing, with more than 300 anti-LGBTQ+ pieces of legislation being considered across the United States as of September 2022 (Anti-LGBTQ+ Bills in 2022Bills in , 2022. Anti-LGBTQ+ legislation has been found to have negative effects on the health and well-being of GM individuals (Horne et al, 2022) and is a particular concern for GM youth and their parents (Abreu et al, 2022;Barbee et al, 2022). Therefore, when GM youth encounter minority stressors in their daily lives, they are doing so within the context of a broader society that is not structured to support them and, in some places, is actively working to undermine them.…”
Section: Minority Stress Theory and Intersectionalitymentioning
confidence: 99%
“…In two additional studies that focused on parents’ perceptions of how their TGD child is impacted by proposed legislation banning GAMC, parents described worrying about their child’s mental health worsening and the increased likelihood that they will experience violence and discrimination (Abreu et al, 2022; Kidd et al, 2021). When reflecting on the impact of the 2016 election, TGD adults reported similar concerns about safety and discrimination.…”
Section: Impact Of the Sociopolitical Context On Mental Health And We...mentioning
confidence: 99%